Penggunaan Interpolasi Bilinier Pada Akuisisi Data Massa - Saputra, Muhammad Ifan; Sulistiyanti, Sri Ratna; Setyawan, F.X. Arinto (Jurnal Teori dan Aplikasi Fisika, 2024)
The bilinear interpolation method is generally used to improve images that have noise. However, in this research the bilinear interpolation method will be used to determine the weight value of a digital scale designed with four load cell sensors. Data collection was carried out by placing loads at nine different points. The loads used are 2kg and 5kg. The results of this research are that the value of the point in the center or on the axis of the four load cells, namely points B, D, E, F, and H, has the same voltage as the actual value, namely for a 2kg weight of 4.31 mV. and for a weight of 5 kg it is 5.87 mV. Meanwhile, the other points, namely points A, C, G and I, have values ​​that deviate from the actual value by 0.36 mV or an error of 36%. Keywords: Bilinear Interpolation, Digital Scales, Load Cell Sensors.